Reinforcement measures to reduce the human induced vibrations on stair steps: a case study - Andrade, Pedro (2022)
The human induced vibrations seen on stairs are usually a global phenomenon, however in some cases, if the connection between the treads and the rest of the structure has a very low rotational stiffness, a so-called local vibration phenomenon can happen, i.e. the vibrations in the treads may be independent from those verified on the staircase that it supports them. This paper presents a case study of a particular metal staircase in which the local vibrations were high. The objective of this study was to measure the vibrations experimentally and then to propose several reinforcement measures in order to reduce them. A total of eight reinforcement measures were proposed, being tested through the construction of several numerical models using the software SAP2000. The numerical accelerations obtained with each reinforcement measure were compared with those obtained initially and with the design guide SCI P354 to verify their effectiveness. The most effective reinforcement measures were those that significantly increased the stiffness of the treads.